Crossover Métrico: a integração de indicadores altmétricos para a análise da produção científica - Silva, Sérgio Salustiano da (2019)
Digital environments offer a multitude of possibilities for the actors involved in research development and funding. Among the new opportunities is the almost real-time monitoring of the repercussion of a scientific content through metrics and indicators that sign a possible relevance and/or interest of the subject addressed to various types of assessments. Within this scope altmetrics emerged as a new subfield of information metrics studies whose purpose is to measure the dissemination of scientific documents on the web and social networks. Studies of its viability and application are still in development phase, and in most cases are compared with several other indicators that have emerged over the years. One of the main features of these alternative metrics is to offer complementary information to the considered traditional metrics. However, even with the increasing popularization of this subfield there is still the need for theoretical and methodological deepening. For this reason, the conceptual and methodological contributions of Cybermetrics were used for the research, being a consolidated subfield and which carries in its scope all the elements that also compose the altmetrics. Thus, the research sought to use the information knowledge that can be extracted from the web and social networks, in addition to taking into account the particularities and quirks of each environment to propose the use of crossover techniques for develop a model that can assist in the information metrics studies. The preliminary results point to the feasibility of using the crossover, at the same time, enabled the development of three index (exposure, interaction and appropriation), which are used as a way to contribute to the studies that seek direct ways of looking at the amount of data made available by and in digital environments.